Fermentation process optimization, analysis of volatile flavor components and non-volatile metabolites of litchi fruit wine - YANG Shanrui, LIU Jun, LI Li, ZHAO Yulin, TU Yilin, LUO Cai, LI Chengjun, NI Bin, LIU Genqiao (Zhongguo niangzao, 2025)
Litchi (Litchi chinensis Sonn.) fruit wine was prepared using fresh litchi as material, and the fermentation process was optimized by single factor and response surface tests using sensory scores as response value. The volatile flavor components and non-volatile metabolites in litchi fruit wine before and after fermentation were analyzed by headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) and liquid chromatography-mass spectrometry (LC-MS). The model was constructed using orthogonal partial least squares discriminant analysis (OPLS- DA), the key differential metabolites were screened by variable importance in projection (VIP) and P values, and the metabolic pathways were analyzed. The results showed that the optimal fermentation process was obtained as follows: fermentation temperature 28 ℃, yeast inoculum 2.5%, initial pH 5.0, and initial reducing sugar content 180 g/L. Under these optimal conditions, the alcohol content and sensory score of litchi fruit wine were 15.64%vol and 92.0 points, respectively. A total of 10 organic acids were detected in litchi fruit wine, and a total of 56 volatile flavor compounds were detected in litchi fruit wine before and after fermentation, including 21 alcohols, 12 esters, 2 aldehydes, 3 acids, 8 alkenes and 10 others. A total of 544 key differential metabolites (VIP≥1, P<0.05) were screened from litchi fruit wine before and after fermentation, of which 334 were up-regulated and 210 were down-regulated. The results of KEGG pathway enrichment analysis showed that the metabolites such as fenugreek and L-malic acid were significantly enriched after fermentation and had potential health care functions, and amino acid biosynthesis pathways played an important role in the formation of characteristic flavors.